PENGEMBANGAN TEKNIK PRODUKSI MASAL BIOMAS ECENG GONDOK - Saadah, Tatuk Tojibatus; Haryanta, Dwi (Universitas Nahdlatul Ulama Sidoarjo, 2016)
Siltation and the presence of water hyacinth plants on a sewer / river is a cause of flooding in urban areas (beaches). Plant fast-growing water hyacinth in rivers, ditches, Boezem, or area lakes and water storage areas, which impede the flow of water, encouraging a silting. Dredging rivers or reservoirs of waste water hyacinths just stacked on the edge of time that makes the environment become rundown. Implementation of the research aims to develop a composting technique made from water hyacinth in a mass scale. Factorial experimental treatment (1) Packaging: open, plastic bags (glansing), and buried; and (2) Starter: EM4, urea, and urea mixture EM4, so there are nine combinations of treatments. Experimental units are water hyacinth biomass as much as one cubic so that a total of nine cubic. Results of the study was to variable volume shrinkage, temperature, pH, change in smell, color and texture of the biomass of water hyacinth showed that during the first two weeks seen a high variation among treatments, but entered the week to five (four weeks after the starter) all variables are relatively homogeneous and shows indicators composting process is almost complete. Depreciation amounted to 68-78% volume, temperature 26-290C, pH of 7.0-7.5; texture is brittle, blackish brown color and relatively odorless. The C / N ratio of biomass at the composting mass of water hyacinth from Rp 33-37 (High), and at week five (four weeks after the starter) the results are varied, for the treatment of S1, S2B1, and S3B1 value is still above 20 (not yet decent) while the other is below 20, and the lowest at 16.9 S3B3 treatment.